2018
DOI: 10.3390/app8081298
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Research on Resilient Modulus of Silty Clay Modified by Oil Shale Ash and Fly Ash after Freeze-Thaw Cycles

Abstract: To dispose of the large amount of OSA (oil shale ash) and FA (fly ash) in Northeast China, a novel subgrade material obtained by modifying SC (silty clay) with OSA and FA was produced. First, the effect of F-T (freeze-thaw) cycles and stress states on the resilient modulus of unmodified SC and the modified SC were investigated. Second, the damage ratio was introduced to describe the relationship of resilient modulus versus F-T cycles. Third, the effect of F-T cycles on the microstructure of soils was investiga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 22 publications
(25 reference statements)
0
19
0
Order By: Relevance
“…Based on the existing research, the dry mass ratio of 2:1:2 for OSA/FA/SC and moisture content of 12.95% are selected to manufacture MSC because, through a series of conventional physical and mechanical property tests conducted by the authors, it was found that, under this ratio, the MSC has great shear strength, the smallest plasticity and the highest CBR value [20,21,29]. Table 2 lists the physical properties of MSC obtained from Refs [20,21,29]. The dry mass ratio of 2:1:2 for OSA/FA/SC and moisture content of 12.95% used in this study can be referred to Refs [20,21,29].…”
Section: Preparation Of Mixed Samples and Testing Samplesmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the existing research, the dry mass ratio of 2:1:2 for OSA/FA/SC and moisture content of 12.95% are selected to manufacture MSC because, through a series of conventional physical and mechanical property tests conducted by the authors, it was found that, under this ratio, the MSC has great shear strength, the smallest plasticity and the highest CBR value [20,21,29]. Table 2 lists the physical properties of MSC obtained from Refs [20,21,29]. The dry mass ratio of 2:1:2 for OSA/FA/SC and moisture content of 12.95% used in this study can be referred to Refs [20,21,29].…”
Section: Preparation Of Mixed Samples and Testing Samplesmentioning
confidence: 99%
“…Table 2 lists the physical properties of MSC obtained from Refs [20,21,29]. The dry mass ratio of 2:1:2 for OSA/FA/SC and moisture content of 12.95% used in this study can be referred to Refs [20,21,29]. Before manufacturing MSC, there are three steps.…”
Section: Preparation Of Mixed Samples and Testing Samplesmentioning
confidence: 99%
“…Turner [18] proved that the silty sand, which was processed with OSA, obtained significant improvement in strength, resilient modulus, and F-T durability. In previous literature, research on soil stabilization with both OSA and FA is inadequate, and it focuses on the author's previous research [11,15,23]. Wei et al [11,23] modified silty clay (SC) by OSA and FA (In the following interpretation, the silty clay, modified by OSA and FA, will be referred to as MC for short), and conducted a battery of laboratory tests to research the mechanical characteristics and environmental impacts of MC; research results showed that the modified SC was suitable for road construction in seasonally frozen areas.…”
Section: Raw Materialsmentioning
confidence: 99%
“…In previous literature, research on soil stabilization with both OSA and FA is inadequate, and it focuses on the author's previous research [11,15,23]. Wei et al [11,23] modified silty clay (SC) by OSA and FA (In the following interpretation, the silty clay, modified by OSA and FA, will be referred to as MC for short), and conducted a battery of laboratory tests to research the mechanical characteristics and environmental impacts of MC; research results showed that the modified SC was suitable for road construction in seasonally frozen areas. Li et al [15] proved the feasibility of using MC and the XPS board as a road subgrade thermal insulation layer, by the numerical modeling and environmental evaluation on an experiment road located in the Jilin province; however, in their numerical modeling, they viewed the specific heat capacity and thermal conductivity of the MC, XPS board, and SC under F-T cycles as a constant value, so their results could not show the real changes of their thermal insulation performance under freeze-thaw cycles, and thus, their research results exaggerated or belittled the thermal insulation effect of the MC and XPS board.…”
Section: Raw Materialsmentioning
confidence: 99%
See 1 more Smart Citation